Effects of Different Water Contents on the Quality Characteristics of Roasted Large Yellow Croaker (Larimichthys crocea) Fillets - Shuting Huang; Shuji Liu; Ping Wen; Xiangyang Lin; Xiaoting Chen; Yongchang Su; Yuping Xie; Huawei Zheng; Yihui Chen; Zhiyu Liu (Foods)
This study investigated the effect of the water content of large yellow croaker fillets on their quality characteristics after roasting. The large yellow croaker fillets were randomly divided into groups, namely, the fresh group (BMC-77), the 3% salt-cured group (BMC-70), and groups cured with 3% salt followed by hot air drying to obtain different moisture contents (BMC-65, BMC-60, and BMC-55). Then, the fillets were roasted at 220 °C for 20 min. There were four replicates for each group. Various indicators, including color, texture, thiobarbituric acid-reactive substance (TBARS) content, total volatile basic nitrogen (TVB-N) content, water distribution, volatile components, and myofibrillar proteins were determined, and a sensory evaluation was carried out. The results showed that as the water content decreased, the lightness (L*) of the roasted fillets significantly decreased (p < 0.05), while the redness (a*) and yellowness (b*) increased. The hardness, shear force, TBARS, and TVB-N values all increased significantly (p < 0.05). The proportion of immobile water decreased, while the proportions of tightly bound water, free water, and loosely bound water increased. The electronic nose, electronic tongue, and GC-MS analyses revealed that there were significant differences in odor, taste, and volatile components among fillets with different water contents. A comprehensive analysis of all the indicators demonstrated that the fillets with an initial water content of 65% (BMC-65) achieved the best sensory qualities after roasting in terms of taste and flavor. An appropriate reduction in the initial water content helped to improve the texture and appearance of the fillets while delaying the degradation of proteins and lipids. This study provides a theoretical foundation for optimizing the roasting process of large yellow croaker fillets. Future research could explore the synergistic effects of the roasting conditions and water content to achieve more accurate quality control.